Association of Endogenous Retroviruses and Long Terminal Repeats with Human Disorders - Katoh, Iyoko; Kurata, Shun-ichi (Frontiers in Oncology, 2013)
Since the human genome sequences became available in 2001, our knowledge about the human transposable elements which comprise ~40% of the total nucleotides has been expanding. Non- LTR (long terminal repeat) retrotransposons are actively transposing in the present-day human genome, and have been found to cause ~100 identified clinical cases of varied disorders. In contrast, almost all of the human endogenous retroviruses (HERVs) originating from ancient infectious retroviruses lost their infectivity and transposing activity at various times before the human-chimpanzee speciation (~6 million years ago), and no known HERV is presently infectious. Insertion of HERVs and mammalian apparent LTR retrotransposons (MaLRs) into the chromosomal DNA influenced a number of host genes in various modes during human evolution. Apart from the aspect of genome evolution, HERVs and solitary LTRs being suppressed in normal biological processes can potentially act as extra transcriptional apparatuses of cellular genes by re-activation in individuals. There has been a reasonable prediction that aberrant LTR activation could trigger malignant disorders and autoimmune responses if epigenetic changes including DNA hypomethylation occur in somatic cells. Evidence supporting this hypothesis has begun to emerge only recently: a MaLR family LTR activation in the pathogenesis of Hodgkin’s lymphoma and a HERV-E antigen expression in an anti-renal cell carcinoma immune response. This mini review addresses the impacts of the remnant-form LTR retrotransposons on human pathogenesis.